Looking at Resilience With a New Eye: A Nomological Network and Model - Bell, Geoffrey G.; Sweetman, Abbey (Journal of Applied Business and Economics, 2022)
Resilience is an interdisciplinary construct examined at individual, group, and organizational levels. This broad disciplinary background has produced disparate and contradictory knowledge. In this paper, we develop a nomological network of resilience and other closely related constructs (agility, flexibility, stability, fragility, and rigidity) to clearly distinguish among these constructs, and thereby, we clearly define each of them. We adopt configurational principles to examine the relationships among these constructs and their antecedents, thereby developing a fuller and richer understanding of the nomological network. Doing so allows us to identify several antecedents to both resilience and its related constructs, allowing managers to focus their attention on “levers” to simultaneously bolster both resilience as well as other constructs that also enhance resilience. Finally, we outline several important paths forward for research.